2012
DOI: 10.3109/15368378.2011.624656
|View full text |Cite
|
Sign up to set email alerts
|

GSM 900 MHz microwave radiation affects embryo development of Japanese quails

Abstract: A wide range of non thermal biological effects of microwave radiation (MW) was revealed during the last decades. A number of reports showed evident hazardous effects of MW on embryo development in chicken. In this study, we aimed at elucidating the effects of MW emitted by a commercial model of GSM 900 MHz cell phone on embryo development in quails (Coturnix coturnix japonica) during both short and prolonged exposure. For that, fresh fertilized eggs were irradiated during the first 38 h or 14 days of incubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
6
0
3
Order By: Relevance
“…The detected changes in the ETC of mitochondria of brain cells cause the metabolic reprogramming of cell mitochondria that increases the rate of superoxide radical generation and the formation of cellular hypoxia. Metabolic reprogramming of mitochondria, which occur under the influence of low-intensity irradiation and irradiation by UHF EMR, causes changes in the functioning of cells [3][4][5][6][7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detected changes in the ETC of mitochondria of brain cells cause the metabolic reprogramming of cell mitochondria that increases the rate of superoxide radical generation and the formation of cellular hypoxia. Metabolic reprogramming of mitochondria, which occur under the influence of low-intensity irradiation and irradiation by UHF EMR, causes changes in the functioning of cells [3][4][5][6][7].…”
Section: Resultsmentioning
confidence: 99%
“…According to modern biophysical and biochemical views, biological membranes are the most vulnerable to the action of ionizing radiation. Radicalcreating centers in ETC of membranes of mitochondria and endoplasmic reticulum initiate the development of chain free-radical reactions with following DNA dysfunction [4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…Bastide exposed chick embryo over the entire period to 900 MHz GSM signal and found that the mortality in the exposed group increases significantly from 16% to 64% (Bastide et al., ). However, Tsybulin showed an increased embryo survival and hatchability in exposed groups of quail eggs after 14 days exposure to a GSM 900 MHz cell phone at 0.2 μ W/cm 2 as compared to sham‐exposed groups (Tsybulin et al., ). These data of the effects on embryo mortality and deformity rate are so different, possibly because of the different radiation parameters and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…of living organisms to EMF has probably occurred in a broad range. There is some in vivo and in vitro experimental evidence of hormetic responses to EMF [4][5][6][7].…”
Section: Review Articlementioning
confidence: 99%